Peran Guru BK dalam Menumbuhkan Kepercayaan Diri pada Siswa Yang Introvert di SMPN 13 Desa Padang Panjang Kabupaten Kaur - Anggreni, Marshela (DAWUH : Islamic Communication Journal, 2023)
The purpose of this study was to discuss the role of counseling teachers in increasing self-confidence for introverted students at SMPN 13 in Padang Panjang Village, Kaur Regency, because it is not uncommon for introverted students to be quite intelligent students but only not confident to show it in front of their friends or in front of the class, therefore counseling teachers must be able to play a role for these students in increasing their self-confidence. The method used in this research is qualitative, namely data obtained through interviews. The results of the study can show what role the counseling teacher will play in increasing the self-confidence of introverted students.